الاستثمارات البيئية وأبعادها الاقتصادية - خضور رسلان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
لقد أثبتت معطيات الواقع أنه لا يمكن معالجة المشاكل البيئية بالوعظ والتعليمات والأوامر والتشريعات فقط، بل لابد من أداة فعالة في إطار السياسة البيئية، وتتجسد هذه الأداة بالاستثمارات البيئية، التي يترتب عليها جملة من الآثار والمنعكسات الاقتصادية. يتناول هذا البحث مفهوم الاستثمارات البيئية وأنواعها وأشكالها والمتطلبات والشروط الواجب توفرها لهذا النوع من الاستثمارات ومصادر تمويلها، إضافة إلى الآثار الاقتصادية المترتبة عليها، كما يتناول واقع وفرص الاستثمارات البيئية في سورية. وقد توصل البحث إلى نتائج تفيد بأن مشروعات الاستثمار البيئي هي ليست مشروعات ذات بعد بيئي فقط، بل مشروعات تنموية لها منعكساتها الاقتصادية في حل مشاكل البطالة والفقر، إضافة إلى حل المشاكل البيئية. وفي ظل ارتفاع أسعار مصادر الطاقة غير المتجددة يصبح الاستثمار في مجال الطاقة البديلة(كاستثمار بيئي) أكثر جدوى من الناحية الاقتصادية إلى جانب جدواها البيئية، وقد تحد الاستثمارات البيئية من النمو في الأمد القصير، إلا أنها تحفز النمو في الأمد الطويل. It has been proved, in fact, that solving environmental problems can not be carried out by giving lectures, instructions, administrative directives and legislations alone. There must be an effective tool within the framework of the environmental policy. This tool is embodied in environmental investments upon which there are a host of economic effects. This research deals with the concept of environmental investments, their different forms, conditions, finances as well as their economic effects. The research also discusses the state, and chances, of environmental investments in Syria. The conclusions of the research have emphasized that environmental investment projects which have their economic dimensions in solving the problems of unemployment and poverty, in addition to solving environmental problems. Moreover, as the prices of irredeemable energy are going up, investment in renewable energy- which is a form of environmental investment- becomes more feasible. Although environmental investments might, in the short term, restrain economic development, they promote, in the long term, economic development.